Qualitative research - Silverman, David 1943- (SAGE, 2016)
A who's who of methodologists, this book introduces students to the big picture of qualitative research, teaching both the 'why' and the 'how to' of getting started, selecting a method and conducting research and data analysis. With practical tips, summaries, exercises and further reading, each chapter is like a masterclass from a leading scholar in qualitative research.